High‐Quality White OLEDs with Comparable Efficiencies to LEDs. Issue 8 (14th February 2018) - Jeon, Sohee; Lee, Sunghun; Han, Kyung‐Hoon; Shin, Hyun; Kim, Kwon‐Hyeon; Jeong, Jun‐Ho; Kim, Jang‐Joo
Abstract: The solid‐state lighting sources require high efficiency and high‐quality illumination at the same time. Here, highly efficient white organic light emitting diodes (WOLEDs) comparable to LEDs are demonstrated using a random vacuum nanohole array and a half‐spherical lens as internal and external light extraction layers, respectively, exhibiting the maximum external quantum efficiency of 78% and luminous efficacy of 164 lm W −1 . These high efficiencies are achieved by extracting all the waveguided and substrate‐confined modes, minimizing surface plasmon polariton loss by elongating the distance from emitting dipole to reflective electrode and selection of phosphorescent dyes having high horizontal emitting dipole ratios. In addition, the WOLEDs satisfy the requirements as a high‐quality lighting source with a high color temperature of 3400 K, the color rendering index of 80, uniform emission pattern, and little variation of color with viewing angle. It is supposed that the present research reaches the ultimate goal of light extraction technology for practical applications. Abstract : High‐performance white organic light emitting diodes (WOLEDs) are realized using a random vacuum nanohole array (VaNHA) in combination with a half‐spherical lens. The simulated mode fraction as a function of the thickness of electron transport layer (ETL) without extraction layers and the measured maximum external quantum efficiencies of WOLEDs without and with VaNHA point to the superior performance.